Conservation tillage mitigates the negative effect of landscape simplification on biological control. Issue 1 (18th October 2015) - Tamburini, Giovanni; De Simone, Serena; Sigura, Maurizia; Boscutti, Francesco; Marini, Lorenzo
Summary: Biological pest control is a key ecosystem service, and it depends on multiple factors acting from the local to the landscape scale. However, the effects of soil management on biological control and its potential interaction with landscape are still poorly understood. In a field exclusion experiment, we explored the relative effect of tillage system (conservation vs. conventional tillage) on aphid biological control in 15 pairs of winter cereal fields (barley and wheat) selected along a gradient of landscape complexity. We sampled the abundance of the main natural enemy guilds, and we evaluated their relative contribution to aphid predation and parasitism. Conservation tillage was found to support more abundant predator communities and higher aphid predation (16% higher than in the fields managed under conventional tillage). In particular, both the abundance and the aphid predation of vegetation‐ and ground‐dwelling arthropods were increased under conservation tillage conditions. Conservation tillage also increased the parasitism rate of aphids. A high proportion of semi‐natural habitats in the landscape enhanced both aphid parasitism and predation by vegetation‐dwelling organisms but only in the fields managed under conventional tillage. The better local habitat quality provided by conservation tillage may compensate for a low‐quality landscape. Synthesis and applications . Our study stresses the importance of considering both soil management and landscape composition when planning strategies to maximize biological control services in agro‐ecosystems, highlighting the role played by conservation tillage in supporting natural enemy communities. In simple landscapes, the adoption of conservation tillage will locally improve biological control provided by both predators and parasitoids mitigating the negative effects of landscape simplification. Moreover, considering the small scale at which both predation and parasitism responded to landscape composition, a successful strategy to improve biological control would be to establish a fine mosaic of crop and non‐crop areas such as hedgerows, tree lines and small semi‐natural habitat patches.